Effects of different edible mushroom hosts on the development, reproduction and bacterial community of Tyrophagus putrescentiae (Schrank). (March 2015) - Qu, S.-X.; Li, H.-P.; Ma, L.; Hou, L.-J.; Lin, J.-S.; Song, J.-D.; Hong, X.-Y.
Abstract: The storage mite, Tyrophagus putrescentiae (Schrank), infests various stored products, plant seeds, chinese herbal medicines and edible mushrooms in China. To assess interactions between edible mushroom hosts and the mite, we investigated the effects of nine species on development and reproduction at 22 °Cand 85% humidity in the laboratory. We also demonstrated changes in the bacterial community of T. putrescentiae reared on four mushroom hosts. All the immature stages, female longevity and reproductive periods were significantly affected by the mushroom species, total immature developmental time varied from 4.41 ± 0.20 (reared on Auricularia polytricha ) to 9.79 ± 0.92 days (when reared on Ganoderma lucidum ). The egg stage was the longest period of the immature stages, whereas the protonymph and tritonymph stages were the shortest at about 2 days. The net reproductive rate ( R 0 ), and the intrinsic rate of increase ( r m ) were significantly different on the nine mushroom hosts. Both the maximum fecundity (212.85 eggs per female) and the highest r m were obtained on A . polytricha . The results indicated that T. putrescentiae had a wide range of adaptability to edible mushrooms, with development and reproduction of the mite being significantly affected by different species. Changes in the bacterial communities inhabiting the mites were influenced by mushroom hosts. A total of 30 full length sequences of 16s rRNA gene were obtained from the mite reared on four hosts. The bacterial community inhabiting T. putrescentiae on A. polytricha host was the most diverse with six different species, two of these genera occurred on Flammulina velutipes host. Consequently the interactions between T. putrescentiae and mushroom hosts can influence both the biological characteristics and bacterial community. The changes of bacterial community might participate in the different fungal mycelium hydrolysis. Highlights: Comparing effects of different edible fungus hosts on the development of mite. Food type significantly affects the reproduction and female longevity of mite. Demographic parameters were different on the different mushroom. Bacterial community inhabiting the mites was changed by the mushroom species.